Upper limb anthropometry, kinematic, and local fatigue in basketball free throw. - Cicchella, A.; D'Adamo, N. (World Congress of Performance Analysis of Sport VIII, 2008)
Major findings of this study are the correlations between fingers lengths and release elbow angle, between grip strength and time of the throw and between arm lengths and time of the movement. These results reflects the needs of movement control necessary for a successful outcome of the free throw in basketball. Previous studies 10 showed the free throw in basketball to be sensitive to local fatigue. In our study the heavy local fatigue protocol (lifting at exhaustion) does not affect the performance while the improvement in score percentage observed after the general fatigue protocol could be attributed to a warm up effect. These latter results suggests that limits to the score performance in the free throw in basketball are not attributable directly to upper limbs fatigue.